Disaster Management in Indonesia: Logistical Coordination and Cooperation to Create Effective Relief Operations - Joost van Rossum; René Krukkert (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2010)
Indonesia has in the past often been struck by natural disasters. After these disasters, the disaster relief operations turned out to be ineffective in most cases. This study focuses on the main problems in disaster relief operations in Indonesia and tries to deliver a general model to deal with those. Literature studies showed that the main problem occurred in the field of organization, communication and logistical processes. Literature studies on relief operations in other countries showed that cooperation with private parties can be effective in these operations. The result of this study is a model which handles with the main problems and has the potential to create effective disaster relief operations.